Exploration of supervision and self-care from the perspectives of palliative care social workers in South Africa - Nyamndaya, Tendayi (Department of Social Development, 2025)
This study explored supervision and self-care from the perspectives of palliative care social workers in South Africa. The study applied a qualitative research design to gather, analyse and present data. The sample comprised of 25 palliative care social workers from private and nongovernmental organisations (NGOs) in South Africa. A non-probability and purposive sampling method was applied as a sampling strategy. A semi-structured interview schedule guide was developed in advance and used as a tool for data collection through in-depth, faceto-face and online interviews with each research participant. The interviews were guided by the overall aim and objectives of the study, which was to explore supervision and self-care from the perspectives of social workers working in palliative care. The study found that supervision and self-care are crucial to palliative care social workers in South Africa. As such, employing organisations need to lead in providing supervision while creating work cultures that support social workers in undertaking different self-care strategies. The study also found that adequately trained and competent social work supervisors should be appointed to supervisory roles, while time and resources should be set aside for self-care activities. When supervision and self-care are supported by top management, they are well received by supervisees who feel more involved, and thus, they prioritise these activities. The study also identified challenges that hinder effective supervision and self-care in palliative care. The study's primary recommendation for supervision is that organisations that employ social workers should provide adequate time and resources and appoint adequately trained and qualified supervisors in palliative care. With regards to self-care, the primary recommendation was that organisations must incorporate self-care activities in the day-to-day work of social workers as well as make time and resources available for various self-care strategies.